Acquired and Congenital Abnormalities of the Pediatric Globe and Optic Nerve - Bhatt, Alok A. (Journal of Pediatric Neuroradiology, 2016)
Abnormalities of the pediatric globe and optic nerve present with different clinical features than adults. While many of these lesions are benign, most have a significant impact on vision, and therefore, the radiologist can play a key role in patient care. This article will review the radiologic features of retinoblastoma, the most common pediatric orbital tumor, as well as other congenital abnormalities such as persistent hyperplastic primary vitreous, Coats disease, and retinopathy of prematurity. Abnormalities of globe development, such as coloboma and vascular lesions, will also be discussed, as these should prompt imaging of the entire neuroaxis due to association with systemic syndromes. Tumors of the optic nerve can also unmask an underlying syndrome, the most common being an optic nerve glioma occurring in the setting of neurofibromatosis type I.
Keywords: globe; optic nerve; retinoblastoma; coloboma; staphyloma; Coats disease; retinopathy of prematurity; persistent hyperplastic primary vitreous